Urgency of Implementing Indonesian Halal Certification in International Trade (Case Study of Chicken Meat Imports from Brazil) - Sukma Hidayatun; Annisa Romadhonia; Miftakhul Janah (JUSTICES: Journal of Law, 2024)
Discussions regarding the halal industry have been very prominent in recent years. Therefore, many issues related to the halal industry are written about and used as research objects. Halal products must have certain specifications so they can play in the halal market. These specifications require certain qualifications that are closely related to halal standards. This research aims to explain the urgency of implementing halal certification in Indonesia in international trade (case study of chicken meat imports from Brazil). The first research result is that as a global food organization, the Food and Agriculture Organization (FAO) has the idea of halal products. Nevertheless, FAO's main focus is currently limited to food products. FAO has not fully protected regulations relating to the guarantee of halal products for countries around the world. FAO provides ratification to each country regarding halal product regulatory policies. The only FAO requirement is that the exporting country must receive halal certification to demonstrate that the product is halal, although this can still be requested by the importing country. The second is that Indonesia has stipulated that although not all products in circulation must have halal certification, some must. Article 135 PP No. 39 of 2021 and Article 125 PP No. 39 of 2021.